Mesenchymal Stem Cell-Derived Exosomes and Their Therapeutic Potential for Osteoarthritis - Kim, Gi Beom (Biology (Basel), 2021)
SIMPLE SUMMARY: Although mesenchymal stem cells (MSCs) have demonstrated their therapeutic potential for osteoarthritis (OA) treatment in preclinical and clinical studies, conventional MSC-based therapies have some limitations that must be overcome. Extracellular vesicles (EVs) are bilayer membrane structures containing bioactive components including proteins, lipids, and RNAs. EVs are classified into exosomes, microvesicles, and apoptotic bodies according to sizes, origins, biomarkers, and compositions. It has been reported that MSC-derived exosomes contain a variety of cytokines, growth factors, and microRNAs, and have comparable anti-inflammatory and regenerative potentials similar to those of MSCs. Here, we review the characteristics and isolation techniques of MSC-derived exosomes and their use for the treatment of osteoarthritis (OA). ABSTRACT: Exosomes are nano-sized vesicles (50–150 nm in diameter) that contain nucleic acids (e.g., microRNA and messenger RNA), functional proteins, and bioactive lipids. They are secreted by various types of cells, including B cells, T cells, reticulocytes, dendritic cells, mast cells, epithelial cells, and mesenchymal stem cells (MSCs). They perform a wide variety of functions, including the repair of damaged tissues, regulation of immune responses, and reduction in inflammation. When considering the limitations of MSCs, including issues in standardization and immunogenicity, MSC-derived exosomes have advantages such as small dimensions, low immunogenicity, and lack of requirement for additional procedures for culture expansion or delivery. MSC-derived exosomes have shown outstanding therapeutic effects through chondro-protective and anti-inflammatory properties. MSC-derived exosomes may enable a new therapeutic paradigm for the treatment of osteoarthritis. However, further research is needed to prove their clinical effectiveness and feasibility.